The faecal abundance of short chain fatty acids is increased in men with a non-dipping blood pressure profile. Issue 4 (21st April 2022) - Huart, Justine; Cirillo, Arianna; Saint-Remy, Annie; Krzesinski, Jean-Marie; de Tullio, Pascal; Jouret, François
Abstract: Background and aims: Gut microbiota (GM) has been involved in the pathophysiology of hypertension (HT), notably via short chain fatty acids (SCFAs). Among the clinical manifestations of HT, the absence of a significant drop in night-time blood pressure (BP) (also known as the non-dipping BP profile) has been associated with poor renal and cardiovascular outcomes. The putative link between GM-derived metabolites and BP dipping status is still unknown. Methods: Male volunteers ( n = 44) were prospectively subjected to 24-hour ambulatory blood pressure monitoring, stool sample collection and a medical questionnaire. Metabolomics analyses of stool samples were conducted using Nuclear Magnetic Resonance (NMR). Results: Higher amounts of acetate, butyrate and propionate were found in the stools of non-dippers ( n = 12) versus dippers ( n = 26) ( p = 0.0252, p = 0.0468, and p = 0.0496, respectively; n = 38 in toto ). NMR spectral data were not interpretable in 5 dippers and 1 non-dipper. A similar significant association was found when including only patients without anti-HT medications ( p = 0.0414, p = 0.0108, and p = 0.0602, respectively; n = 21 in toto ). A not significant trend was observed when focussing only on HT patients without anti-HT medications ( p = 0.0556; n = 14 in toto ). Conclusion: Our pilot study highlights a putative link between GM-derived SCFAs and the BP dipping status, independently of the BP status itself or the anti-hypertensive medications.